2017
DOI: 10.3389/fimmu.2017.00613
|View full text |Cite
|
Sign up to set email alerts
|

Modulating Both Tumor Cell Death and Innate Immunity Is Essential for Improving Radiation Therapy Effectiveness

Abstract: Radiation therapy is one of the cornerstones of cancer treatment. In tumor cells, exposure to ionizing radiation (IR) provokes DNA damages that trigger various forms of cell death such as apoptosis, necrosis, autophagic cell death, and mitotic catastrophe. IR can also induce cellular senescence that could serve as an additional antitumor barrier in a context-dependent manner. Moreover, accumulating evidence has demonstrated that IR interacts profoundly with tumor-infiltrating immune cells, which cooperatively … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
61
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(65 citation statements)
references
References 169 publications
1
61
0
Order By: Relevance
“…This was evidenced by increased mRNA levels for TNFα, IFNγ, IL-6, and IL-23 and higher protein levels for IL-1β and IL-8. While most of the previous studies showed the activation of NFκB p65 for macrophage reprogramming, this last study revealed that IR-induced M1-like phenotype was promoted by the transcriptional expression of IRF5 and was ataxia telangiectasia mutated (ATM)-dependent (107). Altogether, the results from in vitro experiment showed that unpolarized macrophages tend to acquire a M1 phenotype after MDI.…”
Section: Targeting Tams With Rtmentioning
confidence: 72%
See 3 more Smart Citations
“…This was evidenced by increased mRNA levels for TNFα, IFNγ, IL-6, and IL-23 and higher protein levels for IL-1β and IL-8. While most of the previous studies showed the activation of NFκB p65 for macrophage reprogramming, this last study revealed that IR-induced M1-like phenotype was promoted by the transcriptional expression of IRF5 and was ataxia telangiectasia mutated (ATM)-dependent (107). Altogether, the results from in vitro experiment showed that unpolarized macrophages tend to acquire a M1 phenotype after MDI.…”
Section: Targeting Tams With Rtmentioning
confidence: 72%
“…Moreover, modulators of DNA repair, such as Olaparib (PARP inhibitor), increased ATM activation and upregulated IRF5 transcription, resulting in macrophage activation toward a pro-inflammatory phenotype (107). In conclusion, IR is able to induce DNA damage by direct or ROS-dependent interactions with DNA.…”
Section: Targeting Tams With Rtmentioning
confidence: 99%
See 2 more Smart Citations
“…Immune checkpoint blockers such as CTLA-4 and PD-1/PD-L1 enhance the antitumor response induced by radiation therapy (71,74,158163); thus, the interplay between the biological effects of radiation therapy and the immune system may be a critical mechanism for inhibiting tumor growth and extending overall survival in brain metastasis patients. However, the ability to successfully design combination therapeutic strategies is limited due to a lack of understanding of the molecular and cellular mechanisms in radio-oncoimmunology (164). IVM’s spatiotemporal resolution overcomes limitations that constrain other techniques, enabling understanding of immune milieu changes following local or systemic treatment.…”
Section: Examining How Intravital Microscopy Is Used To Study Immmentioning
confidence: 99%